Effects of isoflurane anesthesia on F‐waves in the sciatic nerve of the adult rat. Issue 2 (5th May 2014) - Nowicki, Marcin; Baum, Petra; Kosacka, Joanna; Stockinger, Maximilian; Klöting, Nora; Blüher, Matthias; Bechmann, Ingo; Toyka, Klaus V.
ABSTRACT Introduction Nerve conduction studies provide insights into the functional consequences of axonal and myelin pathology in peripheral neuropathies. We investigated whether isoflurane inhalation anesthesia alters F‐wave latencies and F‐persistence in the sciatic nerve of adult rats. Methods Ten rats were investigated at 3 different isoflurane concentrations followed by ketamine‐xylazine injection anesthesia. To assess F‐wave latencies, a stimulation paradigm was chosen to minimize H‐reflex masking of F‐waves. Results F‐wave persistence rates were reduced with 3.5% isoflurane concentration at 4 and 10 Hz supramaximal stimulation and marginally reduced with 2.5% isoflurane when compared with ketamine‐xylazine. F‐wave amplitudes decreased progressively with rising stimulus frequency in all types of anesthesia and most at 3.5% isoflurane concentration. Conclusions The type of anesthesia and the stimulus repetition rate have an impact on some F‐wave parameters. Higher isoflurane concentrations and repetition rates are not recommended in experimental studies using rat neuropathy models where F‐waves are of interest. Muscle Nerve 50:257–261, 2014